Clinical evaluation of premonitory urges in children and adolescents using the Chinese version of Individualized Premonitory Urge for Tics Scale - Che, Guanghua; Ren, Wenjing; McGuire, Joseph F.; Li, Ping; Zhao, Zhiruo; Tian, Jing; Zhang, Jinyuan; Zhang, Yue (Frontiers in Psychiatry, 2023)
Background：Premonitory urges (PUs) have been the focus of recent efforts to assess the severity and develop interventions for tic disorders (TD). We aimed to investigate the PUs in TD and its comorbidities from multiple dimensions, using the Chinese version of the Premonitory Urge for Tics Scale (C-PUTS) and the Chinese version of the Individualized Premonitory Urge for Tics Scale (C-IPUTS), in order to provide perspectives for the diagnosis and management of TD in children and adolescents. Methods: A total of 123 cases were included in the study. The IPUTS was translated, backtranslated, culturally adjusted, and pre-investigated to determine the items of the C-IPUTS. The reliability and validity of the C-IPUTS scale were evaluated by a questionnaire survey on children and adolescents with TD at the Developmental Pediatrics Department of the Second Hospital of Jilin University. Meanwhile, the C-PUTS, which had been evaluated and used in China, Yale Global Tic Severity Scale (YGTSS), Yale-Brown Obsessive-Compulsive Scale (Y-BOCS), Depression Self-Rating Scale (DSRS), Screen for Childhood Anxiety-Related 2 / 24 2 Disorders (SCARED), Achenbach Child Behavior Checklist (CBCL), and Swanson Nolan and Pelham scale, Version IV (SNAP-IV), were used to assess the association of PUs with tics and comorbidities of TD. Results: All dimensions of the C-IPUTS demonstrated good reliability and validity. Our findings suggested that PUs in children and adolescents in China occurred primarily at the head/face and neck/throat. The different dimensions of the C-IPUTS (number, frequency, intensity) and C-PUTS were positively correlated with the YGTSS total score, while the C-PUTS was positively correlated with the Y-BOCS, SCARED, DSRS, and SNAP-IV scale total scores. The three dimensions of the C-IPUTS demonstrated correlations with anxiety severity and obsessive-compulsive symptoms.The C-IPUTS can be used to assess PUs reliably and effectively and provide further information for the C-PUTS from various dimensions in a Chinese setting. PUs relate to obsessive-compulsive symptoms, anxiety, attention deficit hyperactivity, and behavioral problems in children and adolescents with TDs. Accordingly, PUs evaluation using the C-IPUTS combined with the PUTS might provide useful information for future therapies for TDs to achieve greater tic reduction.